Empowering Posbindu cadres to enhance resilience and improve the economic well-being of elderly women in Dusun Kadilobo, Purwobinangun, Sleman, Yogyakarta - Dewi, Wulan May Kusuma; DW, Sumarni; Kurniawati, Angeline Laurenita; Dewintaputri, Vania; Pratiwi, Indri; Rahmadani, Alfina Nur; Putri, Tri Winarni Soenarto; Ermamilia, Aviria (Faculty of Medicine, Public Health, and Nursing, Universitas Gadjah Mada, 2025)
Introduction: In Dusun Kadilobo, approximately 50 elderly women are facing significant physical, mental, social, and spiritual health challenges as a result of the prolonged eruption of Mount Merapi and the lingering effects of the COVID-19 pandemic. These challenges manifest as increased levels of anxiety and depression, as well as physical ailments such as hypertension and diabetes, further complicated by social and cognitive impairments. Program Kemitraan Masyarakat (PKM) aims to empower posbindu cadres through education, training, and technology based on local product marketing. The program specifically addresses both health—through the development of the “Enhancing the Seven Dimensions of Resilient Elderly” module—and economic struggles faced by elderly women in the area. By empowering Posbindu cadres, the initiative aims to strengthen the resilience of elderly women affected by the eruption and the pandemic, with a focus on food security and product marketing to ultimately improve their economic stability and overall well-being.Methods: The community service project targeted 20 Posbindu Lansia cadres and 30 elderly women in Dusun Kadilobo, Purwobinangun, Pakem, Sleman, conducted from July to September 2023. Research tools included the